(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2011)
In this paper I discuss the notion of transcendentalEmpfindung (transcendental sensation), which plays a central role in Hölderlin’s fragmentary essay Wenn der Dichter einmal des Geistes mächtig ist.Thenotion of transcendental Empfindung is introduced in this essay as a replacement for the concept of intellectual intuition, the well-known philosophical notion which represents one of the key-terms for German philosophers between XVIII and XIX century. In this paper I argue that Hölderlin, having made use of this notion for a long time in his works and philosophical writings, now rejects the intellectual intuition and find a substitute for it in the transcendental sensation under the influence of a renewed reading of Kant’s writings, especially Kant’s Critique of pure reason and Critique of judgement.